Smart load cells: an industrial application - Rocha, J. G. (2000)
This paper presents a data acquisition solution using a RISC type microcontroller with a very few components around, taking advantage of the ratiometric functioning of the load cells. The need of thermally stable circuits is minimized through the use of the same amplification chain for both signal and reference. The amplification and filtering are done trough switched-capacitor techniques controlled by the microcontroller. This option allows the choice of the proper scale according to the platform and permits the auto-calibration of the system. The weighing tests show errors below 100 gr in 400 kg for an industrial platform of 8 smart load cells. The paper also describes an example of software calibration of a multi-load cell weigh-bridge using one processor per smart load cell.